2017
DOI: 10.1016/j.jctb.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Fractional clique decompositions of dense graphs and hypergraphs

Abstract: Our main result is that every graph G on n ≥ 10 4 r 3 vertices with minimum degree δ(G) ≥ (1−1/10 4 r 3/2 )n has a fractional Kr-decomposition. Combining this result with recent work of Barber, Kühn, Lo and Osthus leads to the best known minimum degree thresholds for exact (non-fractional) F -decompositions for a wide class of graphs F (including large cliques). For general k-uniform hypergraphs, we give a short argument which shows that there exists a constant c k > 0 such that every k-uniform hypergraph G on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(76 citation statements)
references
References 24 publications
(40 reference statements)
2
74
0
Order By: Relevance
“…Our argument here and that in [2] is purely combinatorial. In particular, the proofs of Theorems 4.7 and 6.3 together yield a combinatorial proof of Wilson's theorem [30,31,32,33] that every large F -divisible clique has an F -decomposition.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…Our argument here and that in [2] is purely combinatorial. In particular, the proofs of Theorems 4.7 and 6.3 together yield a combinatorial proof of Wilson's theorem [30,31,32,33] that every large F -divisible clique has an F -decomposition.…”
Section: Introductionmentioning
confidence: 54%
“…is given in [7,8] for small values of r and in [2] for large values of r. Theorem 4.6 (Dukes [7,8]). For r ∈ N with r ≥ 2, δ *…”
Section: Fractional and Approximate F -Decompositionsmentioning
confidence: 98%
See 2 more Smart Citations
“…For each r4, Yuster showed that δKr*11/(9r10) and gave a construction showing that δKr*(11/(r+1))n. Dukes used tools from linear algebra to show that δKr*12/(9r2(r1)2), before Barber, Kühn, Lo, Osthus, and the current author were able to generalize and extend Dross's methods for fractional triangle decompositions to show that δKr*11/(104r3/2). In this paper, we show that, for each r4, δKr*11/(100r).…”
Section: Introductionmentioning
confidence: 91%